Workspace analysis in the design parameter space of a 2-DOF spherical parallel mechanism for a prescribed workspace: Application to the otologic surgery. (March 2021) - Chablat, Damien; Michel, Guillaume; Bordure, Philippe; Venkateswaran, Swaminath; Jha, Ranjan
Highlights: Design of mechanism for Otologic Surgery. Kinematic structure of the proposed mechanism. Workspace and Joint space analysis of the proposed 2-DOF Spherical mechanism. Influence of the design parameter on the workspace properties. Workspace without non-singular assembly modes changing trajectories. Abstract: During Otologic surgery, and more broadly during microsurgery, the surgeon encounters several difficulties due to the confined spaces and micro-manipulations. The purpose of the paper is to design a robot with a prescribed regular workspace shape to handle an endoscope to assist the Otologic surgery. A spherical parallel mechanism with two degrees of freedom is analysed in its design parameter space. This mechanism is composed of three legs (2USP-U) to connect the base to a moving platform connected to a double parallelogram to create a remote center of motion (RCM). Its kinematic properties, i.e. the singularity locus and the number of direct kinematic solutions, are investigated. For some design parameters, non-singular assembly modes changing trajectories may exist and have to be investigated inside the prescribed regular workspace shape. Two sets of design parameters are presented with their advantages and disadvantages.